Tingkat Pengetahuan Siswa Kelas VIII tentang Dampak Penggunaan Gadget pada Kesehatan Mata di SMPN 02 Jatiroto-Lumajang - Purwantiwi, Friska Ayu; Sulistyorini, Lantin; Septiyono, Eka Afdi (Pustaka Kesehatan, 2023)
Technology is currently growing more rapidly. Gadgets are not only used by adults but also teenagers and children, especially during the pandemic. Learning activity is conducted online by using gadgets as media. Excessive use of gadgets can harm health, such as impaired vision. Disturbance of vision occurs, namely hypermetropia, myopia, computer vision syndrome (CVS), and asthenopia. A lack of knowledge about the impact of gadget use influences excessive gadget use behavior. This study aimed to determine the level of knowledge of the 7th-grade students on the impact of using gadgets on the eye at Junior High School 02 Jatiroto, Lumajang. The research used descriptive observational 83 respondents involved using a purposive sampling technique. Results showed that as many as 83.1% of students have an enough level of knowledge about the impact of the use of gadgets on the eye. Knowledge is influenced by education, age, interest, experience, work, the cultural environment, and information. Knowledge can be improved by providing information or health education. The study emphasizes the importance of the parent's supervision. It is expected that students use the gadget wisely.